The distribution of DNA repair synthesis in chromatin and its rearrangement following damage with N-acetoxy-2-acetylaminofluorene. - Tlsty, T D (1978)
The distribution of DNA repair synthesis in the chromatin of confluent human diploid fibroblasts damaged with N-acetoxy-2-acetylaminofluorene has been studied. Kinetic analysis of staphylococcal nuclease digestion data revealed that initially most of the repair synthesis occurred in nuclease sensitive regions of chromatin. Continuous labeling experiments and pulse chase experiments indicated that with time much of the 3H dThd initially incorporated into nuclease sensitive regions during repair appeared in nuclease resistant regions. Agarose gel electrophoresis was used to demonstrate that these resistant regions were core DNA. In agreement with previous findings [Smerdon, M.J. and Lieberman, M.W., (1978), Proc. Nat. Acad. Sci. USA, in press], studies of the time course of this rearrangement and of repair synthesis revealed similar time dependences and suggested a relationship between rates of repair synthesis and chromatin rearrangement.